Wearable snow friction measurement device for cross-country skiing - Yu, Z.; Liu, Y.; Hao, Y.; Wu, Y.; Liu, Y.; Zhou, F. (Tribology International, 2024)
Friction on snow surface, especially in relation to winter sports, is difficult to measure directly because of its complexity and variability. In this work, a wearable snow friction measurement device for cross-country skiing was designed and constructed to calculate the friction force and monitor movement signals through the logical placement of three-component sensors and connection parts on skis. Both theoretical simulation and experiments have been conducted, which proved that the deformation of cross-country skis outputs few abnormal force signals during applying large load. Through the static validation in the laboratory, the output accuracy and stability of the device were confirmed. To verify the availability of the device, measurements on a skiing treadmill were conducted, and the results showed that the device can work well and distinguish the different friction behaviors of various waxes. More important, through the ski field test, the device was able to monitor the technical actions and evaluate the frictional coefficient of different ski waxes on snow surface comprehensively, which provides a scientific reference for athletes and coaches in routine training.